The Assistance in the Management of Employee Allocations at UMKM Nanda Tailor, Arjasa Village, Jember Regency - Diah Ayu Retnani Wulandari; Qurrota A'yuni Ar Ruhimat (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Arjasa village has other potential besides agriculture, namely convection. Meanwhile, there is one UMKM Convection that has a managerial problem, namely allocating employees so that the service team decides to solve the problem. The service team carried out a series of service activities using the PRA method which contained socialization and training as well as assistance on how to optimally coordinate and allocate employees by honing the participants' basic skills, namely understanding and understanding the tasks performed and being able to work only in teams. The service team also introduced an assignment method, namely the Hungarian method to help allocate employees. In addition, so that service activities could continue, the service team provided an application to help allocate employees to the convection owner. The application is built using the Hungarian method. With this community service activity, partners can have additional abilities and skills in terms of employee managerial management, especially in creating optimal employee allocations on projects that are being worked on.